Networks in Action Text and Computer Exercises in Network Optimization - Sierksma, Gerard; Ghosh, Diptesh; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Most books covering network optimization explain the theory but offer only exercises that support the understanding of that theory, and case studies that are offered are not suitable for classroom analysis, either because data sets are missing or they$1 (Bre just too large to handle in the classroom. Networks in Action: Text and Computer Exercises in Network Optimization contains a wide range of not-too-large network optimization problems that need to be analyzed and solved by using the computer. Using case studies based on a single fictitious company throughout, the book presents exercises in each chapter that are at once small enough to solve in the classroom, while too large to be solved by eye. After providing an overview of the modeling and implementing process, a look at network theory, and comprehensive listing of references with comments, the book looks shortest paths, minimum spanning trees, network flows, matchings, facility location, and cyclic routing on networks. Each chapter contains exercises that have been rigorously classroom-tested. The result is a perfect text for a one-semester course on network optimization, whether at the advanced undergraduate or the graduate level within an operations research program, econometrics, or as part of an MBA program.s
The Modeling and Implementing Process -- Network Theory -- References with Comments -- Shortest Paths -- Minimum Spanning Trees -- Network Flows -- Matchings -- Facility Location -- Cyclic Routing on Networks -- Erratum.
Keywords: Economics; Computer science; Algorithms; Mathematical optimization; Operations research; Economics/Management Science; Operations Research/Decision Theory; Operations Research, Mathematical Programming; Math Applications in Computer Science; Business/Management Science, general; Optimization; Algorithms